2,6-diaminopurine promotes repair of DNA lesions under prebiotic conditions - Rafał Szabla (Nature Portfolio, 2021)
UV-induced photodamage that likely occurred during the prebiotic synthesis of DNA and RNA is still an untackled issue for their origin on early Earth. Here, the authors show that substitution of 2,6-diaminopurine for adenine enables repair of cyclobutane pyrimidine dimers with high yields, and demonstrate that both 2,6-diaminopurine and adenine nucleosides can be formed under the same prebiotic conditions.